The Potential Role of Individual-Level Benefit-Risk Assessment in Treatment Decision Making: A DIA Study Endpoints Community Workstream. (September 2019) - Reaney, Matthew; Bush, Elizabeth; New, Mary; Paty, Jean; Roborel de Climens, Aude; Skovlund, Soren E.; Nelsen, Linda; Flood, Emuella; Gater, Adam
Benefit-risk assessment is the cornerstone of decision making in medical care, playing a critical role in bringing treatments to market by informing decisions regarding drug development, licensing and reimbursement, and informing treatment decisions made by health care professionals and patients in clinical practice. In regulatory approval decision making, benefit and risk attributes are identified and defined based on available, aggregated clinical data from registration trials. In the context of major developments in recent years for involvement of patients as partners in all phases of drug development and in health care improvement, decision makers increasingly recognize the importance of informing treatment decisions by patient needs, values, experiences, and preferences. Using this as a basis, a DIA workstream was convened to explore the potential of individual-level benefit-risk assessment as a supplement to traditional group-level benefit-risk assessment for evaluating treatment. Various approaches as to how this information could be collected, including via patient-reported outcome measures, open-ended questioning, and stated-preference methods are presented. The utility of this information for various stakeholders is discussed.